STUDI KESESUIAN LAHAN TANAMAN ALPOKAT (Persea Americana Mill) DI KECAMATAN GUNUNG TALANG KABUPETEN SOLOK - Yulianty, Sri Putri; Hermon, Dedi; Juita, Erna (Pendidikan Geografi, 2013)
Suitability focusing on certain plants such as the avocado plant, which is in essence the land suitability analysis is done by combining the avocado crop plants need to grow crops or avocado with land characteristics, this study was conducted in order to investigate and analyze the physical condition of the land (elevation, climate, rainfall, humidity, slope, pH, structure, consistency, organic matter, drainage and soil type), land suitability and spatial distribution corresponding to avocado crops in sub-mountain districts gutter solok. Unit existing landform in the study area consists of four landform units itu. Technique sampling was stratified random sampling is a sampling technique taken strata ( levels). Land analisis unit of data used is descriptive analysis in the form of a comparison table between land characteristics (elevation, climate, rainfall, humidity, slope, pH, structure, consistency, organic matter, drainage and soil type). Compared with the suitability of land for crop avocado. The results showed that the differences in the characteristics of the land that 1. elevation, climate, rainfall, humidity, slope, pH, structure, consistency, organic matter, drainage, and soil type on each landform unit in the mountain district of Solok regency gutter. 2. there is a diversity of land suitability for the avocado crop in the mountain district of Solok regency gutter 3. wide of spatial avocado crop in sub-mountain areas gutter with appropriate mapping f2, f3, f4 and not in accordance with the landform f5. Units appropriate conditions in the study area are in landform unit slope foothills of volcanic plains (f2) with unit slope landform foot volcano (f3) with unit slope landform central volcano (f4) and landform units that do not comply with the volcanic mountain landform units (f5).